HUBUNGAN PERAN PERAWAT SEBAGAI CAREGIVER DENGAN LEVEL OF PATIENT SATISFACTION DI RUANG RAWAT INAP RS BALADHIKA HUSADA JEMBER: The Relationship Between The Role of Nurses as Caregivers and The Level of Patient Satisfaction in The Inpatient Room at Baladhika Husada Hospital Jember - Agustina, Ratna; Dwi Yunita Haryanti; Asmuji (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
One of the most important roles of nurses is as a provider of nursing care that focuses on the patient's healing process and fulfilling health needs holistically. To determine the relationship between the role of nurses as caregivers and the level of patient satisfaction in the inpatient room at Baladhika Husada Hospital, Jember. Quantitative descriptive research design with cross-sectional method. The population in this study were inpatients at Baladhika Husada Hospital Jember during September – November 2023 with a population of 327 patients. The sample used in this study was 85 inpatients. The sampling technique uses Quota Sampling. The results of research on the level of patient satisfaction showed that 91.8% were very satisfied, 3.5% satisfied, 4.7% dissatisfied.  The results of research using the Spearman Rho Rank test (α = 0.05) show that there is a significant relationship between the role of nurses as caregivers and the level of patient satisfaction. The conclusion of this research is that there is a significant relationship between the role of nurses as caregivers and the level of patient satisfaction.